ANALISIS KETERAMPILAN ANAK BUAH KAPAL DALAM MENGHADAPI KEADAAN DARURAT MELALUI SIMULASI PENURUNAN SEKOCI PENOLONG DI KM. SANGIANG - Rigan, Muhammad; Rizal Rochmansyah; Mashartanto, Achmad Ali; Kurniawan, Edi; Setiyawati, Rini (STKIP Subang, 2026)
Passanger ship play an important role in supporting community activities. During voyages, safety equipment is crucial because it must meet the standards set by SOLAS. However, in practice, there are often problems with safety equipment and the skills of the crew themselves. This study aims to identify the factors, constraints, and efforts that influence the skills of crew. The method used in this study is descriptive qualitative, with the research location on the KM. Sangiang ship. The data used is primary data obtained directly through interviews and observations, while secondary data is obtained from ship documents or related reports on board the ship. This study also employed data collection tecchniques such as observation, interviews, and documentation, as well as triangulation data analysis. The result of this duty indicated that the factors and constraints that affect crew skills are crews understanding of lifeboat lowering procedures, discipline, and lifeboat readiness. Efforts made to overcome obstacles include conducting evaluations after drills and improving communication and coordination among crew members.